P631 Treatment of established post-operative recurrence of Crohn's disease with anti-TNF agents: Preliminary data of a multicentre, nationwide study. (16th January 2018) - Cañete, F; Mañosa, M; Barreiro-de Acosta, M; Iglesias, E; Ríos, R; González-Sueyro, R C; Villoria, A; Navarro-Llavat, M; Rodriguez-Lago, I; Taxonera, C; Navarro, P; López, P; et al.
Abstract: Background: Thiopurines are the treatment of choice for the prevention of postoperative recurrence (POR) in Crohn's disease (CD) in high-risk patients, whereas those at low risk should be monitored and treated only in case POR occurs. Endoscopic assessment of POR is recommended within the first year following surgery in all patients. With this strategy, more than 50% of patients will develop POR within 6–12 months after surgery. In patients with established POR, anti-TNF agents may be of benefit, but scarce data on this are available. Methods: Retrospective, multicentre, nationwide study in CD patients who received therapy with anti-TNF agents because of established POR as defined by a Rutgeerts endoscopic score >i1. Epidemiological, clinical, biological and endoscopic features were collected before and after starting anti-TNF. Endoscopic improvement and remission were defined by a reduction in the baseline Rutgeerts score and by a score <i2, respectively. Clinical POR was defined by the presence of two out of the following three criteria: weight loss, increase in stool frequency, and new onset of abdominal pain, in the setting of POR at endoscopy or MRI enterography. Results: 145 CD patients treated with infliximab (69) or adalimumab (76) because of established POR (60% in combination with immunosuppressants) were included. Mean follow-up on anti-TNF: 47 ± 31 months. Table 1 summarises the baseline characteristics. Rates of endoscopic improvement and remission (available in 90 patients; 45 with each anti-TNF. Mean time to endoscopic assessment: 21 ± 22 months), development of clinical POR and surgical POR are shown in Table 2. Multivariate logistic regression analysis showed that infliximab therapy (OR 3.9 95% CI 1.3–11.6), combination thiopurine therapy (OR 4.5 95% CI 1.5–15), and female gender (OR 3.7 95% CI 1.2–11.7) were associated with a higher probability of endoscopic improvement. Conclusions: Anti-TNF therapy constitutes a good option for the treatment of established POR as it achieves endoscopic and clinical improvement in a great proportion of patients. Infliximab seems to be superior to adalimumab in reverting endoscopic lesions in the short-term.